Impacts of Environmental Factors on Pasting Properties of Cassava Flour Mediated by Its Macronutrients - Zhang, Yayuan; Nie, Lei; Sun, Jian; Hong, Yan; Yan, Huabing; Li, Mingjuan; You, Xiangrong; Zhu, Ling; Fang, Fang (Frontiers in Nutrition, 2020)
The impacts of environmental conditions on pasting and physicochemical properties were investigated using flour samples of the same cassava cultivar grown in seven different locations. Significant location differences in essential component (except for fiber) content of cassava flour were observed. Cassava flour showed obviously separated traits in the principal component analysis (PCA) of near-infrared spectra (NIR) according to geographical origins. The environmental effects were significant in the pasting properties of cassava flours. Sufficient precipitation and suitable low temperature promoted accumulation of starch in cassava, resulting in the high peak viscosity values of cassava flour. Pasting temperatures of cassava flour had a significant direct correlation with growth temperature and were negatively correlated with altitude. Precipitation from August to October showed a stronger direct correlation with trough and final viscosity. The results of this study indicated the possibility of predicting and controlling cassava flour quality and pasting properties according to the environmental conditions.